Neutrophil-Associated Inflammatory Changes in the Pre-Diabetic Pancreas of Early-Age NOD Mice - Garciafigueroa, Yesica; Phillips, Brett E.; Engman, Carl; Trucco, Massimo; Giannoukakis, Nick (Frontiers in Endocrinology, 2021)
A growing body of evidence indicates that neutrophils are the first major leukocyte population accumulating inside the pancreas even before the onset of a lymphocytic-driven impairment of functional beta cells in type 1 diabetes mellitus (T1D). In humans, pancreata from T1D deceased donors exhibit significant neutrophil accumulation. We present a time course of previously-unknown inflammatory changes that accompany neutrophil and neutrophil elastase accumulation in the pancreas of the non-obese diabetic (NOD) mouse strain as early as 2 weeks of age. We confirm earlier findings in NOD mice that neutrophils accumulate as early as 2 weeks of age. We also observe a concurrent increase in the expression of neutrophil elastase in this time period. We also detect components of neutrophil extracellular traps (NET) mainly in the exocrine tissue of the pancreas during this time as well as markers of vascular pathology as early as 2 weeks of age. Age- and sex-matched C57BL/6 mice do not exhibit these features inside the pancreas. When we treated NOD mice with inhibitors of myeloperoxidase and neutrophil elastase, two key effectors of activated neutrophil activity, alone or in combination, we were unable to prevent the progression to hyperglycemia in any manner different from untreated control mice. Our data confirm and add to the body of evidence demonstrating neutrophil accumulation inside the pancreas of mice genetically-susceptible to T1D and also offer novel insights into additional pathologic mechanisms involving the pancreatic vasculature that have, until now, not been discovered inside the pancreata of these mice. However, inhibition of key neutrophil enzymes expressed in activated neutrophils could not prevent diabetes. These findings add to the body of data supporting a role for neutrophils in the establishment of early pathology inside the pancreas, independently of, and earlier from the time at onset of lymphocytic infiltration. However, they also suggest that inhibition of neutrophils alone, acting via myeloperoxidase and neutrophil elastase only, in the absence of other other effector cells, is insufficient to alter the natural course of autoimmune diabetes, at least in the NOD model of the disease.